Learning from "All" the faithful: a contemporary theology of the Sensus Fidei - Hinze, Bradford E.; Phan, Peter C. (Pickwick Publications, 2016)
Do various members of the church--regardless of their generation, gender, race, sexual orientation, country of origin, and whatever their doubts are about official church teachings and policies--have any role in determining, safeguarding, and assessing the authentic teaching and praxis of the faith of the church? This has always been a haunting question in the life of the Christian church, though only recently acknowledged, because of the long-standing role of male clergy of European descent with a Eurocentric outlook who held hierarchical offices and determined official doctrines and moral and disciplinary codes. There have been controversies that bear on these matters over the course of the church's history. But it has only been over the last fifty years that the question has received increasing attention among Roman Catholics in terms of the baptismal anointing of the Spirit that bestows the gift of the sense of the faith on individuals and the collective sense of the faithful. This gift provides discerning skills to recognize, receive, and imaginatively and practically apply the living faith in history and society. This book explores these issues from historical, sociological, systematic and theological ethical perspectives, infused by the contributions of world Christianities